Holding familiar: gerenciamento patrimonial e planejamento sucessório - Rossi, Samuel Petry (My University, 2023)
The present scientific work has as its central objective the practical analysis of the issue of succession planning within the national territory, particularly regarding the concept of the family holding. The article begins with a brief exposition on the notion of a holding company and its relevance within Business Law. Subsequently, it delves into the subject of succession planning, culminating in a specific examination of the family holding. In addition to applicable legal and doctrinal understandings, recent jurisprudential rulings on the matter, particularly those issued by the Superior Court of Justice and the Court of Justice of the State of Rio Grande do Sul, will also be highlighted and studied.This study aims to provide a comprehensive and updated overview of succession planning, with a specific focus on the family holding, incorporating both theoretical foundations and practical perspectives. A thorough analysis of legal norms, specialized doctrine, and relevant case law will be instrumental in understanding the legal aspects and significance of this instrument within the context of succession planning. This will serve as a valuable resource for providing accurate guidance and assistance to individuals seeking to implement effective strategies for asset preservation and the continuity of family businesses. Therefore, this work seeks to contribute to a thorough understanding of the topic, exploring the theoretical underpinnings and practical implications of succession planning, particularly within the framework of the family holding. By considering legal principles, scholarly insights, and recent judicial decisions, this study aims to offer valuable insights for professionals and individuals involved in advising and implementing successful wealth preservation and the seamless transition of family businesses. [resumo fornecido pelo autor]
O presente trabalho científico tem como objetivo central a análise prática e aprofundada do planejamento sucessório no âmbito nacional, com destaque para a relevância da figura da holding familiar. Inicialmente, realiza-se uma explanação sucinta sobre o conceito de holding No decorrer do estudo, é concedida especial ênfase à holding familiar como estratégia para a organização patrimonial e gestão dos negócios familiares. Nesse contexto, serão apresentados os aspectos jurídicos relevantes, tais como a constituição da holding familiar, seus principais benefícios e as implicações jurídicas decorrentes dessa modalidade de planejamento sucessório.Além disso, será dada ênfase aos entendimentos jurisprudenciais mais recentes proferidos por órgãos judiciais de destaque, como o Superior Tribunal de Justiça e o Tribunal de Justiça do Estado do Rio Grande do Sul. Essas decisões têm influenciado diretamente a interpretação e aplicação das normas jurídicas relacionadas à holding familiar, trazendo luz aos aspectos práticos e controversos dessa estrutura sucessória. Desse modo, o presente estudo busca proporcionar uma visão abrangente e atualizada sobre o planejamento sucessório com enfoque na holding familiar, integrando as bases teóricas e as abordagens práticas. A análise criteriosa das normas legais, da doutrina especializada e das decisões jurisprudenciais relevantes será fundamental para a compreensão dos aspectos jurídicos e da importância desse instrumento no contexto sucessório, fornecendo subsídios para a correta orientação e assessoria aos interessados na implementação de estratégias eficazes de preservação patrimonial e continuidade dos negócios familiares. [resumo fornecido pelo autor]
Keywords: Herança e sucessão; Empresas familiares - Sucessão